The Characterization of Instant Granule Melinjo Peel (Gnetum gnemon Linn.) as Alternative Treatment for Hyperuricemia - Firdha Senja Maelaningsih; Diah Permata Sari; Andriyani Rahmah Fahriati; Teungku Raviola Saputra; Andika Al Ansori (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Hyperuricemia is a non-communicable disease characterized by high levels of purine in the blood. One of the foods high in purine is melinjo chips. Instant granules from melinjo peel extract with a concentration of 450 mg have been proven to be effective as an anti-hyperuricemia treatment. To ensure the quality of the instant granule preparation, a quality evaluation was conducted to establish it as a new alternative in hyperuricemia therapy. The study aimed to assess the quality of the instant granule preparation of melinjo peel extract, including physical evaluation (particle size, loss on drying, and pH), characterization with Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FT-IR), and specific microbial tests. The test results revealed that the particle size of the instant granules was classified as coarse particles, the Loss on Drying results showed 1.29% granule loss, and the pH evaluation indicated that the granules had a pH of 7.78. Based on the SEM characterization, the granules exhibited non-clumping and heterogeneous morphology. FTIR analysis showed the presence of quercetin in the instant granules of melinjo peel. Specific microbial testing indicated the absence of E. Coli in the preparation. Therefore, it is concluded that the instant granule preparation of melinjo peel has characteristics that make it suitable for development as an instant nutraceutical granule preparation for anti-hyperuricemia treatment.